Professional exhaustion syndrome in health personnel of a public hospital in the Department of Ñeembucu - Argüello, Alejandra; Meaurio, Vanessa; Saucedo, Alicia; Barboza, Sofia; Rolón Ruiz Díaz, Ángel (Medicina Clínica y Social, 2025)
Introduction: Burnout syndrome is a mental and physical wear and tear that cut across any profession and is very prevalent in medical work, it deserves special attention since PAS can lead to a detriment in the quality of the professional functions provided and affect the mental health of health personnel.  Objective: To describe the dimensions of professional burnout syndrome in health personnel in a public hospital in the Department of Ñeembucú in the year 2024.  Methodology: Observational, descriptive, cross-sectional study, from April to September 2024 of a convenience sample where health personnel from the Regional Hospital of Pilar were included and administrative staff were excluded. The standard instrument was applied; Maslach Burnout Inventory Human Services Survey (MBI-HSS) for the study of PAS in its dimensions; emotional exhaustion (EA), depersonalization (DESP) and personal fulfillment (PR). A high score of the AE and DESP dimensions and a low PR score make up the SAP. The continuous variables are expressed as means and standard deviation, and the categorical variables as absolute and relative frequencies.  Results: Of a total of 82 participants, the mean age was 37 years (± 9), with a predominance of 61 (74.39%) females. About 31 (37.80%) participants had PAS, of which women predominated; 25/31(80,6%). The largest proportion of participants were physicians; 45 (54.87%), of these presented the three criteria of PAS; 17 (20.73%) participants. Emotional exhaustion was mostly presented by 14/31 (45.16%) participants, followed by depersonalization 10/31 (32.25%) participants. Conclusion: In the population studied, emotional exhaustion is the most frequently affected dimension and with a predominance of female medical personnel.